Sistem Pakar Identifikasi Penyakit Kulit Melanoma dengan Metode Teorema Bayes - Nopi Purnomo; Riko Muhammad Suri; Devi Yuliana; M. Rasyid (Universitas Putra Indonesia YPTK Padang, 2023)
Melanoma is a skin cancer disease that occurs due to abnormal growth of melanocytes, which are cells that can produce pigment in the skin. Melanoma is one of the most vicious skin cancers and can easily spread to other organs in the human body, such as the lungs and brain. This expert system for diagnosing melanoma skin disease is a computer-based system that is used as a tool for diagnosing melanoma skin disease based on a dynamic knowledge base. The purpose of this research is to build an expert system that can identify Melanoma Skin Disease. An expert system built using the Bayes theorem method in a diagnostic process based on expert knowledge or experience. The results of this study present an expert system capable of diagnosing melanoma skin disease quickly, precisely and accurately. These results are presented in a system built in the form of a website using PHP programming with a MySQL database. Overall this expert system can be useful for patients or the general public to be able to know clearly about melanoma skin disease from the symptoms and can provide solutions in handling it.